2011
DOI: 10.1016/j.brainres.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-mediated inflammation may damage the brain circuit that regulates food intake

Abstract: Adiposity is associated with chronic low-grade systemic inflammation and increased inflammation in the hypothalamus, a key structure in feeding behavior. It remains unknown whether inflammation impacts other brain structures that regulate feeding behavior. We studied 44 overweight/obese and 19 lean individuals with MRI and plasma fibrinogen levels (marker of inflammation). We performed MRI-based segmentations of the medial and lateral orbitofrotal cortex (OFC) and hippocampal volumes. Gray matter (GM) volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 43 publications
(46 reference statements)
10
84
0
3
Order By: Relevance
“…A second study noted that individuals with longstanding type 1 diabetes had significantly reduced FA relative to matched controls; moreover, in the diabetic individuals, longer disease duration and poorer glucose regulation was correlated with reduced FA (Kodl et al 2008). A third study linked adiposity to reduced white matter integrity on DTI (Cazettes et al 2011); this and another study found associations between decreased white matter integrity and increases in markers of systemic inflammation that commonly accompanies cerebrovascular dysfunction (Wersching et al 2010). While these studies may have implications for the hypothesis that at least part of the age-associated declines in white matter integrity may be driven by the effects of hypertension, type two diabetes, obesity, and other cardiovascular risk factors even in the absence of an acute cerebrovascular event, a great deal more study is required to further substantiate this view.…”
Section: Cerebrovascular Dysfunctionmentioning
confidence: 99%
“…A second study noted that individuals with longstanding type 1 diabetes had significantly reduced FA relative to matched controls; moreover, in the diabetic individuals, longer disease duration and poorer glucose regulation was correlated with reduced FA (Kodl et al 2008). A third study linked adiposity to reduced white matter integrity on DTI (Cazettes et al 2011); this and another study found associations between decreased white matter integrity and increases in markers of systemic inflammation that commonly accompanies cerebrovascular dysfunction (Wersching et al 2010). While these studies may have implications for the hypothesis that at least part of the age-associated declines in white matter integrity may be driven by the effects of hypertension, type two diabetes, obesity, and other cardiovascular risk factors even in the absence of an acute cerebrovascular event, a great deal more study is required to further substantiate this view.…”
Section: Cerebrovascular Dysfunctionmentioning
confidence: 99%
“…35 The importance of forebrain integrity in obesity develop ment is substantiated by the association between obesity and the loss of grey matter in these cortical regions. [36][37][38] Whether the loss of grey matter follows or predates obesity is still under investigation. Obesity, at least in its visceral form, might induce cortical thinning, 36 which could be secondary to inflammatory processes.…”
Section: Cortical Executive Circuitsmentioning
confidence: 99%
“…Obesity is related to type II diabetes, hypertension, dyslipaedaemia and cardiovascular diseases (CVD) 1,2,3,7,8 . The endocannabinoid system (ECS) is involved in lipid metabolism and obesity.…”
Section: Obesity and Health Hazardsmentioning
confidence: 99%
“…Adiposity is associated with chronic low-grade systemic inflammation as well as increased inflammation of the hypothalamus. Inflammation of hypothalamus may reduce the integrity of structures involved in reward and feeding behaviours 8 and this may alter the feeding behaviors.…”
Section: Obesity and Health Hazardsmentioning
confidence: 99%